Analysis of Influence of Hinge Condition on Overall Mechanical Performance of Hollow Slab Beam. Issue 4 (May 2019) - Yantao, Du; Jingpeng, Wang; Bo, Peng
Abstract: The concrete hinge joint is a widely used connection method for the assembled hollow slab bridge, and it is also a place where the disease is extremely easy to appear. Through the study of four different simplified calculation modes of the hinge joint, the transverse distribution coefficient of the hollow slab beam under different working conditions is compared and analyzed, and the influence of the hinge joint on the overall mechanical performance of the structure under different working conditions is obtained. It is found that the difference of the simplified mode has a great influence on the calculation of the lateral distribution of the bridge; the complete failure of the joint will lead to a drastic change in the lateral distribution coefficient of adjacent hollow slab beams, and even the phenomenon of single beam appear. At the same time, combined with the research results, reasonable suggestions for the design stage and actual operation stage of hinge joint of the hollow slab beam are put forward.